Targeted Muscle Reinnervation: Considerations for Future Implementation in Adolescents and Younger Children. Issue 6 (June 2018) - Zuo, Kevin J.; Willand, Michael P.; Ho, Emily S.; Ramdial, Sandra; Borschel, Gregory H.
Abstract : Summary: Prosthetic options for patients with proximal upper limb absence are limited. Current above-elbow prostheses may restore basic motor functions for crucial activities, but they are cumbersome to operate, lack sensory feedback, and are often abandoned. Targeted muscle reinnervation is a novel surgical procedure that enhances the ability of patients with above-elbow amputations to intuitively control a myoelectric prosthesis. By transferring multiple severed peripheral nerves to a robust target muscle, targeted muscle reinnervation restores physiologic continuity and enables more intuitive prosthetic control. Although reports have been limited to adults, targeted muscle reinnervation has great potential for application in a pediatric population with congenital or acquired proximal upper limb absence. In this review, the authors describe the rehabilitative challenges of proximal upper limb amputees and outline the objectives, techniques, and outcomes of targeted muscle reinnervation. The authors then discuss important considerations for adapting targeted muscle reinnervation to pediatric patients, including cause of upper limb absence, central plasticity, timing of prosthesis fitting, role of the family, surgical feasibility, and bioethical aspects. The authors believe that carefully screened school-age children and adolescents with bilateral proximal upper limb absence, and select adolescents with unilateral proximal upper limb absence, should be seriously considered for targeted muscle reinnervation performed by an experienced surgical and rehabilitation team. Abstract : This and Related "Classic" Articles Appear on Prsjournal.com for Journal Club Discussions.